Theorizing violence as an essential by-product of the dialectic of enlightenment: reading inglourious busterds as an evidence of the paradox of modernity - Hapugoda, M. (University of Jaffna, 2012)
One of the most important ideological observations made in the latter half of the previous century was the unsolved problem of the paradoxical dialectic existence between the promises made through mega socio-political theories about a better humanity and the violent means to achieve those ends. On one hand, the over-determined textbook dialogue of prosperity through symbolic order and, on the other, the co-existence of underground evil of power through social violence equated the ‘harmonious totality’ of the modern project. If the world is a carefully calculated phenomenon of the Enlightenment man and the reason is the fundamental driving force, it is paradoxical that evil becomes a by-product in the modern post-enlightenment humanity. The Frankfurt School rightly pointed out the necessary co-existence of symbolic law and authority and the obscene supplement of reasonless violence as a fundamental paradox of the post-enlightenment modern project. The bourgeois humanity of the enlightenment project, therefore, carries the characteristic that educated, cultured, mannered and charming men are fully capable of metamorphosing into monstrous beasts within a second. The twentieth century political circumstances witness that the ‘dialectic totality’ of both good and evil is the ‘true history’ of the modern world and its spiritual crisis is obvious through the dual existence of its own products. To illustrate the dialectic existence of the ‘modern project’, the movie Inglorious Busterds (2009) by Quentin Tarantino can be considered as a unique example where the violence portrayed in the movie displays how the ‘decent’ political space has been taken over by the ‘diabolic evil’ of obscene underground or of unconscious real. Through the characters, conversations and events depicted in the movie, this paper investigates how the people who immerse in ‘cultivated academic environments’ are capable of justifying violence over fellow human beings, despite whatever said about their conscience. In relation to this, the discursive practices of the Sri Lankan government in and after the forth Eelam war will be considered as a real life example whenever necessary. In addition, the dirty function of the fantasy as unconscious real, aestheticized violence and de-historization (or alternative history) through a plastic reality will also be discussed as brand new ideological developments.
Keywords: Dialectic of enlightenment; Theorizing violence; Aestheticized violence